Effect of Sodium Bicarbonate on Systolic Blood Pressure in CKD: A Systematic Review and Meta-Analysis. Issue 4 (9th April 2023) - Beynon-Cobb, Beverley; Louca, Panayiotis; Hoorn, Ewout J.; Menni, Cristina; Padmanabhan, Sandosh
Visual Abstract: Abstract : Background: Individuals with CKD are at a higher risk of cardiovascular morbidity and mortality. Acidosis is positively correlated with CKD progression and elevated systolic BP. Sodium bicarbonate is an efficacious treatment of acidosis, although this may also increase systolic BP. In this systematic review and meta-analysis, we summarize the evidence evaluating systolic BP and antihypertensive medication change (which may indicate systolic BP change) in response to sodium bicarbonate therapy in individuals with CKD. Methods: Medical Literature Analysis and Retrieval System Online, Excerpta Medica database, Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, Cochrane Central Register of Controlled Trials, and World Health Organization (WHO) trials registry databases were searched for randomized control trials where sodium bicarbonate was compared with placebo/usual care in CKD stage G1–5 non–dialysis-dependent populations. Random effects meta-analyses were used to evaluate changes in systolic BP and BP-modifying drugs after sodium bicarbonate intervention. Results: Fourteen randomized control trials (2110 individuals, median follow-up 27 [interquartile range 97] weeks, mean age 60 [SD 10] years, mean systolic BP 136 [SD 17] mm Hg, mean eGFR 38 [SD 10] ml/min, mean serum bicarbonate 22 [SD 4] mmol/L) were eligible for inclusion. Meta-analysis suggested that sodium bicarbonate did not influence systolic BP in individuals with CKD stage G1–5. Results were consistent when stratifying by dose of sodium bicarbonate or duration of intervention. Similarly, there was no significant increase in the use of antihypertensive medication or diuretics in individuals taking sodium bicarbonate, whereas there was a greater decrease in antihypertensive medication use in individuals taking sodium bicarbonate compared with controls. Conclusions: Our results suggest, with moderate certainty, that sodium bicarbonate supplementation does not adversely affect systolic BP in CKD or negatively influence antihypertensive medication requirements.